The Physical Activity Patterns of Pregnant Taiwanese Women. Issue 4 (December 2016) - Lee, Ching-Fang; Hwang, Fang-Ming; Lin, Hsien-Ming; Chi, Li-Kang; Chien, Li-Yin
ABSTRACT: Background: Physical activity reduces the risk of maternal disorders during pregnancy. However, many pregnant women reduce their levels of physical activity while pregnant. Purpose: The purpose of this study was to examine and compare the physical activity (total amount, intensity, type) of Taiwanese women during each trimester. Methods: This cross-sectional survey used purposive sampling to enroll 581 Taiwanese women as participants. The physical activity of participants was measured using the Mandarin version of the Pregnancy Physical Activity Questionnaire. Results: The levels of household/caregiving activity and occupational activity differed significantly across trimesters. Household/caregiving (43.2%–54.5%) and occupational activity (42.0%–54.0%) accounted for the largest percentages of total energy expenditure for all three trimesters. In terms of total and household/caregiving activities, multiparous women had significantly higher mean energy expenditures than their primiparous peers. Moreover, income had a pervasive influence on all types and amounts of physical activity and energy expenditures, respectively, with the exception of sports/exercise. Conclusions/Implications for Practice: Further careful assessment of the types and intensities of physical activity that are suitable for pregnant women in different parity and income categories in Taiwan is necessary. Furthermore, healthcare providers should encourage pregnant women to use strategies that promote their more regular participation in enjoyable physical activities. One of these potential strategies is to do activities together with children, family members, or friends.